2024
DOI: 10.14814/phy2.15925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐intensity intermittent exercise versus moderate‐intensity continuous exercise on renal hemodynamics assessed by ultrasound echo

Shotaro Kawakami,
Tetsuhiko Yasuno,
Saki Kawakami
et al.

Abstract: High‐intensity intermittent exercise (HIIE) has become attractive for presenting a variety of exercise conditions. However, the effects of HIIE on renal function and hemodynamics remain unclear. This study aimed to compare the effects of HIIE and moderate‐intensity continuous exercise (MICE) on renal hemodynamics, renal function, and kidney injury biomarkers. Ten adult males participated in this study. We allowed the participants to perform HIIE or MICE to consider the impact of exercise on renal hemodynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…They revealed that MIIE and MICE in hot environments caused an increase in the biomarkers of kidney injury. Furthermore, we recently examined the acute effects of HIIE and MICE on AKI biomarkers in temperature-controlled conditions and demonstrated that glomerular or proximal tubular injury was not induced following a single bout of HIIE or MICE (Kawakami et al 2024). Exercise-induced increases in AKI biomarkers appear to be dependent on the intensity or duration of exercise and the surrounding environment and have been shown to influence AKI biomarkers, which is primarily attributed to a greater magnitude of hyperthermia and hypovolaemia (Schlader et al 2017; Chapman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They revealed that MIIE and MICE in hot environments caused an increase in the biomarkers of kidney injury. Furthermore, we recently examined the acute effects of HIIE and MICE on AKI biomarkers in temperature-controlled conditions and demonstrated that glomerular or proximal tubular injury was not induced following a single bout of HIIE or MICE (Kawakami et al 2024). Exercise-induced increases in AKI biomarkers appear to be dependent on the intensity or duration of exercise and the surrounding environment and have been shown to influence AKI biomarkers, which is primarily attributed to a greater magnitude of hyperthermia and hypovolaemia (Schlader et al 2017; Chapman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Participants avoided strenuous exercise the day before testing, fasted 8 h prior to testing (drinking water was acceptable), and avoided breakfast, caffeine, and exercise on the test day. Although the MICE condition included data from previous study (Kawakami et al 2024), the purpose of that study was to compare the effects of high-intensity intermittent exercise and MICE on renal haemodynamic parameters, whereas the purpose of this study was the effects of continuous or intermittent exercise on renal haemodynamics during moderate-intensity exercise. Therefore, this study excluded duplicate publication.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we state that the assessment of renal hemodynamics using Doppler ultrasonography was performed immediately after exercise, not during exercise (Kawakami et al., 2024 ). At the beginning, we tried to assess renal hemodynamics using Doppler ultrasonography during exercise.…”
mentioning
confidence: 99%
“…However, As the kidneys move with respiration and body movement, breathing needs to pause when assessing the renal hemodynamics, this makes it difficult to assess renal hemodynamics with high accuracy during exercise. Therefore, the assessment of renal hemodynamics using Doppler ultrasonography was performed immediately after exercise rather than during exercise (Kawakami et al., 2018 ; Kawakami et al., 2022 ; Kawakami et al., 2023 ; Kawakami et al., 2024 ; Kotoku et al., 2019 ). Considering that, as authors point out (Chapman et al., 2024 ), renal vascular resistance returns to resting levels within 40 s after stopping exercise (Endo et al., 2008 ), the present data may not strictly reflect renal hemodynamics during exercise.…”
mentioning
confidence: 99%